Stress-Induced Microstructural Alterations Correlate With the Cognitive Performance of Rats: A Longitudinal in vivo Diffusion Tensor Imaging Study - Nagy, Szilvia Anett; Vranesics, Anett; Varga, Zsófia; Csabai, Dávid; Bruszt, Nóra; Bali, Zsolt Kristóf; Perlaki, Gábor; Hernádi, István; Berente, Zoltán; Miseta, Attila; Dóczi, Tamás; Czéh, Boldizsár (Frontiers in Neuroscience, 2020)
BACKGROUND: Stress-induced cellular changes in limbic brain structures contribute to the development of various psychopathologies. In vivo detection of these microstructural changes may help us to develop objective biomarkers for psychiatric disorders. Diffusion tensor imaging (DTI) is an advanced neuroimaging technique, which enables the non-invasive examination of white matter integrity and provides insights to the microstructure of pathways connecting brain areas. OBJECTIVE: Our aim was to examine the temporal dynamics of stress-induced structural changes with repeated in vivo DTI scans and correlate them with behavioral alterations. METHODS: Out of 32 young adult male rats, 16 were exposed to daily immobilization stress for 3 weeks. Four DTI measurements were done: one before the stress exposure (baseline), two scans during the stress (acute and chronic phases) and a last one 2 weeks after the end of the stress protocol (recovery). We used a 4.7T small animal MRI system and examined 18 grey and white matter structures calculating the following parameters: fractional anisotropy (FA), mean diffusivity (MD), axial (AD) and radial diffusivity (RD). T2-weighted images were used for volumetry. Cognitive performance and anxiety levels of the animals were assessed in the Morris water maze, novel object recognition, open field and elevated plus maze tests. RESULTS: Reduced FA and increased MD, RD values were found in the corpus callosum and external capsule of stressed rats. Stress increased RD in the anterior commissure and reduced MD and RD in the amygdala. We observed time dependent changes in several DTI parameters as the rats matured, but we found no evidence of stress-induced volumetric alterations in the brains. Stressed rats displayed cognitive impairments and we found numerous correlations between the cognitive performance of the animals and between various DTI metrics of the inferior colliculus, corpus callosum, anterior commissure and amygdala. CONCLUSIONS: Our data provide further support to the translational value of DTI studies and suggest that chronic stress exposure results in similar white matter microstructural alterations that have been documented in stress-related psychiatric disorders. These DTI findings imply microstructural abnormalities in the brain, which may underlie the cognitive deficits that are often present in stress-related mental disorders.